Global Interreligious Dialogue: Diplomasi Kultural Dalam Kebijakan Dialog Agama Bilateral Indonesia - Tyas Pramudita Indraning (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2020)
This study analyse Indonesia's cultural diplomacy through inter-state religious dialogue. Specifically, this study aims to find out the background of Indonesian cultural diplomacy, bilateral dialogue between religions and cultures and Indonesian bilateral diplomacy. Diplomacy is a way, with certain manners, that is used by a country to achieve the country's national interests in relations with other countries or with the international community. In the context of the former effectiveness of diplomacy, it requires political or economic support or a real economic, political, and military power, but now we know what is called cultural diplomacy, which in fact economic, political and military forces in certain cases is "counter productive". Bilateral dialogue is a conversation between two countries or more in an international discussion forum to improve cooperative relations in the economic, social, political, cultural and religious fields in the framework of creating a harmonious and peaceful religious life in the world including overcoming various global issues indicated threatening world security. Cultural diplomacy is part of public diplomacy (soft power diplomacy) with economic and cultural cooperation. Soft Power is the ability to get what you want by inviting and attracting the sympathy of others.